2020
DOI: 10.1080/1331677x.2020.1752277
|View full text |Cite
|
Sign up to set email alerts
|

The impact of customer personality and online brand community engagement on intention to forward company and users generated content: palestinian banking industry a case

Abstract: Personality five characteristics are playing crucial role on intention to forward Online Company Generated Content and user generated content mediated by online brand community engagement. This paper is applied on a case of banking industry in order to perceive a long run relationship between banks operating in Palestine and their customers. The total of 685 valid questionnaires were collected from online banking sector in Palestine, who is member of online brand community in Facebook. Moreover, the data were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 61 publications
0
9
0
Order By: Relevance
“…We have contributed to the literature in several ways. First, we have systematically investigated the effect of personality traits on user feedback willingness by considering as many motivation factors as possible, which is in contrast with previous research that did not consider motivation factors [11] or only consider single motivation factor [12]. Our research discovered the personality traits of the willing users and evident feedback motivation factors, which provided theoretical support for the establishment of an effective feedback platform.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have contributed to the literature in several ways. First, we have systematically investigated the effect of personality traits on user feedback willingness by considering as many motivation factors as possible, which is in contrast with previous research that did not consider motivation factors [11] or only consider single motivation factor [12]. Our research discovered the personality traits of the willing users and evident feedback motivation factors, which provided theoretical support for the establishment of an effective feedback platform.…”
Section: Discussionmentioning
confidence: 99%
“…As we know, individual differences in behavior and attitude can be determined by the differences in multiple psychological characters, such as personality traits and cognitive styles, mediated by motivation factors [9,10]. A few papers have studied the effect of personality traits on user feedback behavior without taking the motivation factors into consideration or only consider single motivation factor [11,12]. Certain researchers have investigated how cognitive styles influence some online behaviors, such as multimedia perception, online information searching, and creative behavior [13][14][15][16], but few have directly discussed the influence of cognitive styles on user feedback.…”
Section: Introductionmentioning
confidence: 99%
“…, 2019). Similarly, Yasin et al. (2020) found that individuals who were highly open to creative and novel ideas were more willing to engage in OBCs than those scoring low on the openness trait.…”
Section: Research Background and Conceptual Frameworkmentioning
confidence: 88%
“…A user's content contribution was measured from two perspectives: the active degree and the emotional expression tendency of that contribution which correspond to four variables: 𝑡𝑜𝑡𝑃𝑜𝑠𝑡 𝑖𝑡 , 𝑝𝑜𝑠𝑃𝑜𝑠𝑡 𝑖𝑡 , 𝑛𝑒𝑔𝑃𝑜𝑠𝑡 𝑖𝑡 and 𝑛𝑒𝑢𝑃𝑜𝑠𝑡 𝑖𝑡 . In previous studies, reposting behavior, the number of microblogs reposted by users in a given period, was taken as a control variable to supplement users' content contribution (Cox et al, 2009;Yasin et al, 2020). However, while reposting behavior affects the creation of users' original content, users' content contribution also has an impact on the probability of their content being reposted by others.…”
Section: Empirical Modelmentioning
confidence: 99%